1992
DOI: 10.1063/1.108061
|View full text |Cite
|
Sign up to set email alerts
|

Selective growth of Si/SiGe resonant tunneling diodes by atmospheric pressure chemical vapor deposition

Abstract: Selective SiGe and heavily As doped Si deposited at low temperature by atmospheric pressure chemical vapor deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Our microstructures were fabricated of p-Si/Si 1Ϫx Ge x RTD material grown at Tϭ550-600°C by atmospheric pressure chemical vapor deposition ͑CVD͒ on a p ϩ -Si substrate. 12,13 The undoped active region consists of a narrow Ϫ35 Å Si 0.75 Ge 25 well clad by Ϫ45 Å Si barriers. The active region is, in turn, sandwiched between undoped Ϫ100 Å thick Si 0.75 Ge 0.25 layers and then Ϫ100 Å Si 1Ϫx Ge x layers in which the Ge content is graded down to pure Si and the doping is gradually increased to match the p ϩ -Si substrate and top contacting layers.…”
mentioning
confidence: 99%
“…Our microstructures were fabricated of p-Si/Si 1Ϫx Ge x RTD material grown at Tϭ550-600°C by atmospheric pressure chemical vapor deposition ͑CVD͒ on a p ϩ -Si substrate. 12,13 The undoped active region consists of a narrow Ϫ35 Å Si 0.75 Ge 25 well clad by Ϫ45 Å Si barriers. The active region is, in turn, sandwiched between undoped Ϫ100 Å thick Si 0.75 Ge 0.25 layers and then Ϫ100 Å Si 1Ϫx Ge x layers in which the Ge content is graded down to pure Si and the doping is gradually increased to match the p ϩ -Si substrate and top contacting layers.…”
mentioning
confidence: 99%
“…These roomtemperature values are significantly larger than reported PVCR values for epitaxial Si tunnel diodes at any temperature. [5][6][7][8][9][10][11][12][13][14]17 It is observed that V p shifted to larger values with higher anneal temperature. The plot of V p vs I p was linear.…”
mentioning
confidence: 97%
“…The triple-barrier RTS's used for these measurements were grown by atmospheric pressure chemical vapor deposition on silicon substrates. 15 The active region consists of two undoped Si/Si 0.8 Ge 0.2 wells with nominal widths W 1 ϭ35 Å and W 2 ϭ28 Å separated by a narrow middle barrier of undoped Si of nominal width Lϭ10, 20, and 30 Å for the three different structures and clad by 35-Å outer barriers of undoped Si. There are 200-Å undoped Si/Si 0.8 Ge 0.2 spacer layers graded to p ϩ -Si contact regions on either side of the active region.…”
mentioning
confidence: 99%
“…We have fabricated device mesas down to a lateral extent of 5 m using conventional metallization and etching techniques. 15 When a bias V is applied between the contact regions at low temperatures T, current flows by hole tunneling from the valence band of the strained Si 0.8 Ge 0.2 emitter region into the coupled subbands of the Si 0.8 Ge 0.2 double-well structure. Figure 1 shows a typical tunneling I(V) characteristic for a triple-barrier RTS with Lϭ20 Å, which exhibits wellresolved resonant peaks at Vϭ215 and 500 mV.…”
mentioning
confidence: 99%